Detecting the interest of undergraduate students : A new way of chemistry education as a basis for instructional development - Parham Saadi; Almubarak Almubarak; Restu Prayogi; Fadhlan Muchlas Abrori (Jurnal Pendidikan Kimia, 2024)
The achievement of learning targets is largely determined by how learning facilitates the needs of participants. Interest is one of the important points that teachers need to be aware of, especially in higher education environments to produce competent and resilient students (prospective teachers). The purpose of the research was to detect the interests of chemistry education students quantitatively and other themes that related to their lives. The quantitative approach was the method used in the study because it was in line with the data collection technique, namely the questionnaire technique with quantitative analysis. The results showed that the theme interest œeveryday life with the topic of food has the largest percentage, namely 86%, while the least theme was textile dyeing (58.30%) by chemical processes theme. Other additional themes revealed that social media (digital technologies) has 75.50% while teaching & learning and diversity have percentages of 64.70% and 59%, respectively. The conclusion was that detecting elements of interest in students could be supporting data for designing chemistry learning considering the changes in the mindset of the young generation due to digital culture. This research can also be used as a needs analysis in learning because a great interest in learning affects students™ academic performance. Research findings also give be a provision for students when they become teachers so that this research can be used in the school environment.